Effect of fly ash as partial cement replacement properties of lightweight concrete subjected to air curing - Intan Suraya, A. Rahim (2018)
Fly ash and palm oil boiler stone are waste product that causes environmental pollution. Thus, this research study is to investigate the effect of fly ash as partial cement replacement on workability, compressive strength and flexural strength of lightweight concrete subjected to air curing. Five mixtures were used in this research. The mix containing 100% cement would act as a control specimen. The rest of the mixes contained various percentage of fly ash which are 10%, 20%, 30% and 40%. The samples were subjected to air curing. Compressive strength and flexural strength conducted at 7, 14 and 28 days. The results revealed that the workability increases with the increase in the use of fly ash content. For both compressive strength and flexural strength, it shows that fly ash concrete is much higher than the concrete without fly ash. The mix containing 10% of fly ash recorded the highest strength value compared to other percentage of fly ash concretes at 28 days. The results showed that we can partially replace the cement with the waste material, therefore we can reduce the emission of carbon dioxide into the atmosphere and save natural material.